Association of ABCB1 Polymorphisms with Efficacy and Adverse Drug Reactions of Valproic Acid in Children with Epilepsy - Jiahao Zhu; Jieluan Lu; Yaodong He; Xianhuan Shen; Hanbing Xia; Wenzhou Li; Jianping Zhang; Xiaomei Fan (Pharmaceuticals, 2023)
Genetic polymorphisms in ATP-binding cassette subfamily B member 1 (ABCB1, also known as MDR1) have been reported to be possibly associated with the regulation of response to antiseizure medications. The aim of this study was to investigate the association of ABCB1 polymorphisms with the efficacy of and adverse drug reactions to valproic acid among Chinese children with epilepsy. A total of 170 children from southern China with epilepsy treated with valproic acid for more than one year were recruited, including 61 patients with persistent seizures and 109 patients who were seizure-free. Two single nucleotide polymorphisms of ABCB1, rs1128503 and rs3789243, were genotyped using the Sequenom MassArray system. The two single nucleotide polymorphisms of ABCB1 were found to be significantly associated with treatment outcomes of valproic acid in children with epilepsy. Carriers with the TT genotype of ABCB1 rs1128503 were more inclined to exhibit persistent seizures after treatment with valproic acid (p = 0.013). The CC genotype of rs3789243 was observed to be a potential protective factor for valproic acid-induced gastrointestinal adverse drug reactions (p = 0.018), but possibly increased the risk of valproic acid-induced cutaneous adverse drug reactions (p = 0.011). In contrast, the CT genotype of rs3789243 was associated with a lower risk of valproic acid-induced cutaneous adverse drug reactions (p = 0.011). Haplotype analysis showed that CC haplotype carriers tended to respond better to valproic acid treatment (p = 0.009). Additionally, no significant association was found between ABCB1 polymorphisms and serum concentrations of valproic acid. This study revealed that the polymorphisms and haplotypes of the ABCB1 gene might be associated with the treatment outcomes of valproic acid in Chinese children with epilepsy.